Is the prevention and/or cure of autism a morally legitimate quest? - Bovell, V (2015)
The thesis explores the ethical questions underlying important contemporary debates about how society should respond to autism; whether autism is 'disease', 'disability' or 'difference', and whether it requires 'treatment' or 'acceptance'. Part 1 comprises a historical overview of how knowledge about autism has evolved through the perspective of contrasting stakeholders – clinicians and researchers, parents, professionals, the neuro-diversity movement. It reviews the main areas of academic ethical discussion to date with regard to autism, and proposes a new analytic framework – structured in terms of six 'categories of intervention': from pre-conceptual measures to post-birth interventions targeted towards infants and adults, and from individuals through to wider societal measures. Part 2 then conducts an ethical analysis using this framework. Examples are offered at each stage of intervention, along with a discussion of the ethical questions posed at each one. Part 3 reflects on the questions to which Part 2 has given rise, addressing the way ethical positions on how to respond to autism rely on wider views about quality of life and wellbeing; parental virtues; the impact of local decisions on wider states of affairs (the Big Conundrum); and views on "where autism sits" in comparison with other conditions (the Analogy Challenge). It is argued that to conflate autism and suffering is to fail to do justice to extreme variations among autistic people, and disguises the extent to which external barriers may be the main obstacles to flourishing for autistic people and their families. The real-life conditions in which autistic people and their families struggle for recognition and support are therefore held to be of crucial significance for making both global and localised ethical judgements. It is therefore concluded that cure and/or prevention are not morally defensible as global targets for autism as a whole, but should be clearly distinguished from the ethical importance of supportive and therapeutic interventions to address particular problems that autistic individuals may have. The implications, for research and practice, are spelled out, with particular emphasis on the need for further dialogue among all stakeholders.